2014
DOI: 10.1039/c4nj00084f
|View full text |Cite
|
Sign up to set email alerts
|

Optical, electrical and microstructural studies of monoclinic CuO nanostructures synthesized by a sol–gel route

Abstract: We have reported on the synthesis of CuO nanostructures via a simple sol-gel approach with high yield at low cost by the reduction of aqueous solutions of Cu(NO 3 ) 2 and Na 2 NO 3 . Synthesized nanostructures were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), fluorescence spectroscopy, Raman scattering and UV-Vis-NIR spectroscopy.Structural studies revealed that the prepared CuO nanostructures were polycrystalline in nature with monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…5, respectively. From the SEM image of the CuO nanoparticles it is seen that the particles occur in a form of elongated nanorod-type structure [29] and the particle sizes of the observed nanoparticles are in the range of 10 to 30 nm. The obtained nanoparticle sizes are in close proximity with the crystallite size calculated using XRD data.…”
Section: Sem Analysismentioning
confidence: 99%
“…5, respectively. From the SEM image of the CuO nanoparticles it is seen that the particles occur in a form of elongated nanorod-type structure [29] and the particle sizes of the observed nanoparticles are in the range of 10 to 30 nm. The obtained nanoparticle sizes are in close proximity with the crystallite size calculated using XRD data.…”
Section: Sem Analysismentioning
confidence: 99%
“…For example, Dhanasekaran et al, prepared nanostructured CuO using copper nitrate and sodium carbonate as precursors by sol-gel route. 20 They have used 0.4 M sodium carbonate and 0.2-0.6 M copper nitrate. Lin et al, investigated variation of band gap of size-controlled ZnO quantum dots by sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the increase of copper content in the nanostructures. The prepared thin films exhibited good optical properties [32]. Bibi Figure 7(b,c) [34].…”
Section: Figurementioning
confidence: 95%
“…The copper oxide nanostructures were synthesized using 0.2 and 0.6 M copper nitrate concentrations by a sol-gel method [32]. The X-ray diffraction pattern revealed that the prepared structures are polycrystalline in nature.…”
Section: Figurementioning
confidence: 99%